Cell therapy of heart pathologies - Lukash, L.L. (Інститут біохімії ім. О. В. Палладіна НАН України, 2008)
The review article is devoted to cellular cardiomyoplasty as a novel technology of treatment of cardiac insufficiency. The experiments on animals and the first clinical trials have shown the possibility to improve the contractile function of diseased heart after transplantation of different types of donor cells: ardiomyocytes, bone marrow enriched by hematopoietic stem cells and mesenchymal stem cells. The problems of cellular cardiomyoplasty are discussed. Оглядова стаття присвячена клітинній кардіоміопластиці як новій технології лікування серцевої недостатності. Експерименти на тваринах і перші клінічні випробування показали можливість поліпшення скорочувальної функції ураженого міокарда після трансплантації різних типів клітин: кардіоміоцитів, кісткового мозку, збагаченого гемопоетичними стовбуровими клітинами, а також мезенхімальних стовбурових клітин. Обговорюються проблеми клітинної кардіоміопластики. Обзорная статья посвящена клеточной кардиомиопластике как новой технологии лечения сердечной недостаточности. Эксперименты на животных и первые клинические испытания новой технологии показали возможность улучшения сократительной функции пораженного миокарда после трансплантации различных типов клеток: кардиомиоцитов, костного мозга, обогащенного гемопоэтическими стволовыми клетками, а также мезенхимальных стволовых клеток. Обсуждаются проблемы клеточной кардиомиопластики.